Enhancing Standardized Practices for Oral Mucositis Prevention in Pediatric Hematopoietic Stem Cell Transplantation: A Best Practice Implementation Project - Zhang L; Luo Y; Long J; Yin Y; Fu Q; Wang L; Patil S (Dove Medical Press, 2024)
Luyang Zhang,1,* Yuan Luo,1,* Jiewen Long,1 Yan Yin,1 Qin Fu,2 Lei Wang,1 Sandip Patil1 1Department of Haematology and Oncology, Shenzhen Children's Hospital, Shenzhen, Guangdong Province, People's Republic of China; 2Department of Nursing, Shenzhen Children's Hospital, Shenzhen, Guangdong Province, People's Republic of China*These authors contributed equally to this workCorrespondence: Sandip Patil; Lei Wang, Department of Haematology and Oncology, Shenzhen Children's Hospital, 7019 Yitian Road, Shenzhen, Guangdong Province, People's Republic of China, Tel +86-755-83008283, Email sandippatil1309@yahoo.com; 405112310@qq.comBackground: Oral mucositis (OM) poses a significant challenge in children undergoing hematopoietic stem cell transplantation (HSCT). There is a gap between clinical practice and the evidence, and nursing practices is not standardized.Objective: This study aims to evaluate the effectiveness of applying the evidence for preventing HSCT chemotherapy-induced OM in children and to elevate the nurses' compliance to the evidence.Methods: Following the clinical evidence practice application model of the Joanna Briggs Institute (JBI) evidence-Based Care Center. The process included reviewing literature, extracting evidence, identifying gaps, developing audit criteria, conducting a baseline audit, creating an action plan, implementing evidence-based interventions, and assessing outcomes.Results: After the evidence implementation, 6 out of 12 audit criteria with poor compliance are significantly improved, with statistically significant differences (P< 0.05). The incidence of OM decreases, with a statistically significant difference (66.6% vs 36.7%, P=0.02). The incidence of grade I, II, III, and IV OM also decreases (30% vs 23.3%, 23.3% vs 13.4%, 10% vs 0%, and 3.3% vs 0%). Ultimately, the standardized oral care practice routine and workflows to prevent OM were established.Conclusion: Bridging the gap between evidence and clinical practice can standardize nurse behavior, decrease the incidence of OM, and lower the OM severity in children undergoing HSCT.Keywords: children, hematopoietic stem cell transplantation, oral mucositis, evidence-based practice